1
$\begingroup$

A guideline on which identity to use would be greatly appreciated, as $1-\cos2A=2\sin^2A$ identity isn't giving me the correct answer I think.

Given that:

$$\zeta = {\frac {1-\cos4(\theta) + i \sin4(\theta)} {\sin2(\theta)+ 2i\cos^2(\theta)}} $$

To prove:

$$|\zeta| = 2\sin(\theta) \qquad\text{and}\qquad \arg(\zeta) = \theta $$

My work so far;

Proof:

$$\zeta = {\frac {\sqrt{(1-\cos4\theta)^2 + \sin^24(\theta)}} {\sqrt{\sin^22(\theta)+ 4\cos^4(\theta})}} $$

I'm not sure about the above, if there's an easy explanation or method to go through would be great as questions like these are giving me a bit of trouble.

$\endgroup$
  • 2
    $\begingroup$ The stated result is incorrect if $\sin\theta<0$. $\endgroup$ – J.G. Jul 20 at 18:00
  • $\begingroup$ @J.G. you're correct, there seems to be a typo in the question rather than mine, as I tried it with two methods and both times $\arg(\zeta) = \theta$ returns a $-\theta$ $\endgroup$ – Ryuk Jul 20 at 18:35
  • $\begingroup$ We need $|\zeta|=2|\sin\theta|$, while $\arg\zeta=(-\theta+\pi[\sin\theta<0])(\mod 2\pi)$. $\endgroup$ – J.G. Jul 20 at 18:36
  • $\begingroup$ math.stackexchange.com/questions/3298570/… $\endgroup$ – lab bhattacharjee Jul 20 at 18:54
1
$\begingroup$

Method 1: Using the $1-\cos2A=2\sin^2A$ identity

For $|\zeta| = 2\sin(\theta)$:

$$\zeta = {\frac {|1-\cos4(\theta) + i \sin4(\theta)|} {|\sin2(\theta)+ 2i \cos^2(\theta)|}} $$

$$\zeta = {\frac {\sqrt{(1-\cos4\theta)^2 + \sin^24(\theta)}} {\sqrt{\sin^22(\theta)+ 4\cos^4(\theta})}} $$

$$\zeta = {\frac {\sqrt{(1-2\cos4\theta + \cos^24\theta+\sin^24\theta}} {\sqrt{4\sin^2\theta\cos^2\theta+ 4\cos^4(\theta})}} $$

$$\zeta = {\frac {\sqrt{(2-2\cos4\theta}} {\sqrt{4\cos^2\theta(\sin^2\theta+ \cos^2(\theta}))}} $$

$$\zeta = {\frac {\sqrt{2}\sqrt{1-\cos4\theta}} {2\cos\theta}} \begin{cases} \mbox{$1-\cos2A=2\sin^2A$ identity} \end{cases} $$

$$\zeta = {\frac {\sqrt{2}\sqrt{2\sin^22\theta}} {2\cos\theta}} $$

$$\zeta = {\frac {2\sin2\theta} {2\cos\theta}} $$

$$\zeta = {\frac {2\sin\theta\cos\theta} {\cos\theta}} = 2\sin\theta.$$

For $\arg(\zeta) = \theta$:

$$\arg(\zeta) = \arg(1-\cos4\theta+i\sin4\theta)-\arg(\sin2\theta+2i\cos^2\theta)$$

$$\arg(\zeta) = \arctan(\frac{\sin4\theta}{1-\cos4\theta})-\arctan(\frac{2\cos^2\theta}{\sin2\theta})$$

$$\arg(\zeta) = \arctan(\frac{2\sin2\theta\cos2\theta}{2\sin^22\theta})-\arctan(\frac{2\cos\theta\cos\theta}{2\sin\theta\cos\theta})$$

$$\arg(\zeta) = \arctan(\cot2\theta)-\arctan(\cot\theta)$$

$$\arg(\zeta) = \arctan[\tan(90°-2\theta)]-\arctan[\tan(90°-\theta)])$$

$$\arg(\zeta) = 90°-2\theta-90°+\theta$$

$$\arg(\zeta) = -\theta.$$

Method 2: Using De Moivre's theorem,

$$\zeta = {\frac {1-\cos4(\theta) + i \sin4(\theta)} {\sin2(\theta)+ 2i \cos^2(\theta)}} $$

$$\zeta = {\frac {2\sin^22\theta + i 2\sin2\theta\cos2\theta} {2\sin\theta\cos\theta+ 2i \cos^2\theta}} $$

$$\zeta = {\frac {2\sin2\theta(\sin2\theta + i\cos2\theta)} {2\cos\theta(\sin\theta+ i \cos\theta)}} $$

$$\zeta = {\frac {2\sin\theta\cos\theta(\sin2\theta + i\cos2\theta)} {\cos\theta(\sin\theta+ i \cos\theta)}} * {\frac{-i}{-i}}$$

$$\zeta = {\frac {2\sin\theta(\cos2\theta - i\sin2\theta)} {\cos\theta - i \sin\theta}}$$

$$\zeta = {\frac {2\sin\theta[(\cos-2\theta + i\sin-2\theta)]} {\cos(-\theta) + i \sin(-\theta)}}$$

$$\zeta = {\frac {2\sin\theta(\cos\theta+i\sin\theta)^{-2}} {(\cos\theta+i\sin\theta)^{-1}}} \begin{cases} \mbox{De Moivre's Theorem} \end{cases} $$

$$\zeta = 2\sin\theta[\cos(-\theta)+i\sin(-\theta)]$$

$$|\zeta| = 2\sin(\theta) \qquad\text{and}\qquad \arg(\zeta) = -\theta $$

$\endgroup$
2
$\begingroup$

Hint:$$\zeta=\frac{2(\sin2\theta)(\sin2\theta+i\cos2\theta)}{2(\cos\theta)(\sin\theta+i\cos\theta)}=\frac{2\sin 2\theta\cdot ie^{-2i\theta}}{2\cos\theta\cdot ie^{-i\theta}}=2\sin\theta e^{-i\theta}.$$

$\endgroup$
0
$\begingroup$

Note that\begin{align}\bigl(1-\cos(4\theta)\bigr)^2+\sin^2(4\theta)&=2-2\cos(4\theta)\\&=2-2\bigl(1-2\sin^2(2\theta)\bigr)\\&=4\sin^2(2\theta)\\&=16\sin^2(\theta)\cos^2(\theta)\end{align}and that\begin{align}\sin^2(2\theta)+4\cos^4(\theta)&=4\sin^2(\theta)\cos^2(\theta)+4\bigl(1-\sin^2(\theta)\bigr)^2\\&=4\sin^2(\theta)-4\sin^4(\theta)+4-8\sin^2(\theta)+4\sin^4(\theta)\\&=4\bigl(1-\sin^2(\theta)\bigr)\\&=4\cos^2(\theta)\end{align}and that therefore$$\lvert\zeta\rvert^2=\frac{\bigl(1-\cos(4\theta)\bigr)^2+\sin^2(4\theta)}{\sin^2(2\theta)+4\cos^4(\theta)}=4\sin^2(\theta).$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.